The Silence: What It Is and How To Use It - Bush, David V. (David Van), 1882-1959 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Silence: What It Is and How To Use It" by David V. Bush is a self-help publication written in the early 20th century. This work focuses on the concept of "Silence" as a therapeutic and spiritual practice that enables individuals to achieve mental clarity and physical well-being through right thinking and meditation. It explores the relationship between thought, health, and harmony, suggesting that one's mental state can profoundly influence their overall life experience. In this book, Bush lays out various methods for entering the Silence, emphasizing the importance of mental relaxation and positive affirmations. He describes the Silence as a space where individuals can reach a deeper connection with the divine, facilitating healing and re-harmonization of the body and mind. The text serves as a guide for those seeking to transform their thinking patterns to foster health, success, and abundance in their lives. Through practical exercises and affirmations, readers are encouraged to let go of negative thoughts and embrace a mindset conducive to positive change and personal growth. (This is an automatically generated summary.)
Release date is 2004-08-08
E-text prepared by Juliet Sutherland, Keith M. Eckrich, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Psychology, Applied; New Thought